CATCH DISTRIBUTION AND BIOLOGICAL CHARACTERISTICS OF DIAMONDBACK SQUID (THYSANOTEUTHIS RHOMBUS) OFF NORTHEAST CEBU ISLAND, PHILIPPINES - Lamayo, Roberto C; Cuñado, Venerando D; Delan, Gloria G; Rica, Rachel Luz V; Ilano, Anthony S; Lamayo, Ma. Helian A (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
This study examines the catch distribution of Diamondback Squid (Thysanoteuthis rhombus) in northeast Cebu, the physical characteristics of its habitat and its biological characteristics. Catch rates were monitored to determine its seasonal occurrence. Data were collected using squid jigs, a nautical chart, Nansen bottles, a refract meter, and a thermometer. Data collection involved pre-survey activities, establishing a study site, plotting the grid levels, measuring water temperature and salinity, and determining the moon phases and biological characteristics of captured squid. Data were collated and analyzed statistically using analysis of variance and regression. Catches were highest near Carmen at 100 30-36’N and 1200 05-11’E. Catches occurred at 1-50 m depth, and were highest in July.